PEMBINAAN JAMAAH TABLIGH MELALUI PENGUATAN MODAL SOSIAL DI KOTA PALU - Thalib (Paedagogia: Jurnal Pendidikan, 2019)
Fostering of Muslims in particular is a necessity. Muslims need guidance to stay on their nature, namely peace, calm, and peace (congratulations). Therefore, to maintain and preserve the atmosphere (peaceful, calm, serene), then one of the da'wah movements that has taken a role is the Tablighi Jamaat. Forms of coaching that have been done include syuro (deliberation), ta'awun (help-help). The coaching is intended to be social capital in developing Muslims. Social capital is intended as an adhesive tool for the community, because it often occurs in Islamic internal conflict communities that will affect external conflicts (among religious believers). The formation of Muslims by the followers of Tabligh has clearly brought developments to Muslims, especially in the city of Palu, this development was marked by an increase in the number of halaqah from 2 halaqah (2001) to 12 halaqah (2018), and the development has benefited the community based at the mosque.